Active cutaneous leishmaniasis in Brazil, induced by Leishmania donovani chagasi - M. P. Oliveira Neto; Gabriel Grimaldi Junior; Hooman Momen; R. S. Pacheco; Mauro Celio de A. Marzochi; D. McMahon Pratt (Memorias do Instituto Oswaldo Cruz, 1986)
L.d. chagasi was isolated from active cutaneous leishmaniasis in both human and canine infections in an endemic area in Rio de Janeiro, Brazil. Both isolates were identified by molecular and immunological characterization of the parasite using three different methods: electrophoretic mobility of isoenzymes; restriction endonuclease fragment analysis of kDNA and serodeme analysis using monoclonal antibodies. This seems to be the first well documented case in the New World of a "viscerotropic" Leishmania inducing a case of cutaneous leishmaniasis. This observation emphasizes that the diagnosis of the etiologic agent of human or canine visceral leishmaniasis based solely upon clinical and epidemiological critwria may lead to erroneous conclusions. Em lesões cutâneas, de um caso humano e de um cão, procedente de área endêmica de leishmaniose tegumentar no Rio de Janeiro, foi isolada L.d. chagasi. Ambas as culturas foram identificadas por caracterização molecular e immunológica do parasito utilizando três diferentes métodos: mobilidade eletroforética de isoenzimas, análise do kDNA e anticorpos monoclonais. Este parece ser o primeiro caso humano bem documentado, no Novo Mundo, de uma Leishmania "viscerotrópica" induzindo lesões cutâneas e demonstra que o diagnóstico do agente etiológico baseado somente na observação clínica e dados epidemiológicos pode levar a conclusões errôneas.